Proposed Work Text in Teaching and Learning Communication Arts for Freshman College Students - Romel R. Costales (Randwick International of Education and Linguistics Science Journal, 2022)
Teaching and learning English can be most successful with developed instructional materials that are research-based. This study investigated the grammatical competencies of college freshman students with the end-in-view of proposing a worktext in teaching/learning communication arts. The study used descriptive analysis method. 64 freshman students enrolled in English 11a (Communication Arts and Skills 1) were used as participants. Results revealed that the freshman students’ grammatical competencies improved from “fairly competent” before exposure to the modules to “competent” after exposure. Moreover, findings indicated that there was significant difference in the competency level in grammar of the respondents before and after exposure to the worktext. This means that after using the worktext, the students’ level of competence in grammar greatly improved. Hence, the worktext as an instructional material in teaching/learning communication arts is effective.